The impact of socio-economic factors on the youth unemployment-the case of republic of north Macedonia - Petkovski, Vladimir; Petkovska Mirchevska, Tatjana; Daniloska, Natasha; Boshkovska, Diana (Institute of Economic Sciences Belgrade, 2019)
The main objective of the paper is to determine the socio-economic factors that influence youth unemployment in the Republic of North Macedonia. The findings are based on the Principal Component Analysis (PCA) of vital socio-economic indicators that influence the problem of youth unemployment. In particular, the goal of the research is to identify the connections of several socio-economic indicators that reflect the situation of youth unemployment in the Republic of North Macedonia.